Azotobacter improves shelf-life of tomato (Lycopersicon esculentum) - CHAURASIA, C N S; DE, NIRMAL; SINGH, K P; KALLOO, G (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1996--99 at Varanasi to characterize visual shelf-life of tomato (Lycopersicon esculentum Miller nom. cons.) under ambient condition as influenced by genotypic variation and on-farm biofertilizer treatment. Soil application of Azotobacter @ 15 kg/ha coupled with N, P and K@ 150,60 and 80 kglha: influenced the pericarp thickness, shelf-life and yield positively in 8 tomato hybrids (,BSS 99', 'ARTH 128', 'Gotya', 'ARTH 16', 'SC 2','SC 28','Himlata' and' ARTH 4') in Inceptisol. Soil application of Azotobacter enhanced the shelf-life of tomato by 3-5 days when harvested at breaker stage. The soil application + seedling inoculation with Azotobacter before transplanting significantly prolonged the shelf-life of tomato at least for 2 days, depending on variety than by alone soil application, The combined application of phosphate-solubilizing bacteria and Azotobacter was not as effective in enhancing the shelf-life of tomato as the alone application of Azotobacter. Total soluble solid (%) was significantly improved under the influence of Azotobacter, while phosphate-solubilizing bacteria did not influence significantly. Yield and quality in terms of shelf-life, pericarp thickness and total soluble solid (%) were found better in hybrid 'BSS 99' compared with the 7 other tested hybrids.